The land and people of Russia - Nazaroff, Alexander (J.B. Lippincott New York, 1966)
An introduction to the history, geography, people, political and economic development, and way of life of the vast and diverse country known as the Union of Soviet Socialist Republics.
Includes Index
Keywords: Soviet Union -- Juvenile literature